2007
DOI: 10.1167/iovs.06-1371
|View full text |Cite
|
Sign up to set email alerts
|

MMP and TIMP Expression in Quiescent, Dividing, and Differentiating Human Lens Cells

Abstract: PURPOSE.Matrix metalloproteinases (MMPs) and the tissue inhibitors of the MMPs (TIMPs) have been implicated in lens differentiation, growth, remodeling, and cataract. Hence, a gene expression analysis was undertaken in epithelial and fiber cells dissected from clear human donor lenses. METHODS. The human lens was dissected into three regions: anterior epithelial, equatorial, and fiber cells. Primary lens cell cultures were also analyzed. cDNA was generated by reverse transcription of the mRNA portion of the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…The role of MT6-MMP remains to be determined, but MT2-MMP is expressed in human anterior lens epithelium along with MT1-MMP, MT3-MMP, MT4-MMP, and MT5-MMP. 24 A study by Morrison et al 46 using TIMP2 knockout mice fibroblast cells revealed that heightened levels of MT2-MMP were sufficient to activate pro-form MMP2 despite the lack of TIMP2. This was dependent on MMP2 binding to the cell surface via the hemopexin domain most likely by association with integrin avb6.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of MT6-MMP remains to be determined, but MT2-MMP is expressed in human anterior lens epithelium along with MT1-MMP, MT3-MMP, MT4-MMP, and MT5-MMP. 24 A study by Morrison et al 46 using TIMP2 knockout mice fibroblast cells revealed that heightened levels of MT2-MMP were sufficient to activate pro-form MMP2 despite the lack of TIMP2. This was dependent on MMP2 binding to the cell surface via the hemopexin domain most likely by association with integrin avb6.…”
Section: Discussionmentioning
confidence: 99%
“…23 This study also demonstrated that the broadspectrum MMP inhibitor GM6001 and a specific MMP2/9 inhibitor reduced the formation of TGFb-induced ASC. 23 MT1-MMP (MMP14) expression is also reported in the lens 24 and is generally proposed to play a role in the activation of MMP2 through proteolytic cleavage to remove the pro-domain. 25 MT1-MMP, pro-form MMP2, and tissue inhibitor of matrix metalloproteases 2 (TIMP2) form a trimolecular complex, 26 which results in removal of the inhibitory pro-domain from MMP2 by an adjacent free MT1-MMP molecule.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…20,51 Unlike other MMPs, MMP-2 is constitutively expressed by many cell types. 52 Although expression of MMP2 is low within the native human lens and requires disruption to invoke upregulation, 53 our results showed that chicken LECs expressed MMP-2 in the absence of stimulation. The high levels of MMP-2 expression seen in many tissues suggest that the regulation of proenzyme activation is more relevant for the control and induction of MMP-2 action than that of other members of the MMP family in which transcriptional control is more important.…”
Section: Discussionmentioning
confidence: 58%
“…58 MT2-MMP is expressed in the human lens and primary lens cell cultures. 53 These results suggest that different mechanisms may involve MMP-2 activation in LECs.…”
Section: Discussionmentioning
confidence: 87%